PERANCANGAN JARINGAN HOTSPOT BERBASIS MIKROTIK ROUTER OS 3.3.0 - Ilham Eka Putra (ITP Press, 2013)
Most of people using the internet as a basic requirement tool in this job. A many applications has been grown up internet access especially. Recently, Internet access with use of hotspot is much popular. A Hotspot requirement did not longer a cable too much to be able share data. Since the Hotspot used signal. So at this point much liked cause of cheaper than a subscription Internet access on an individual ISP package. MikroTik RouterOS ™, a base Linux operating system intended as a network router. A Designing to provide convenience for users. Administration can be done through the Windows Application (Winbox). In addition to the installation can be done on a Standard PC (Personal Computer). PC that will be used as proxy router did not require substantial resources for the use of standards, for example, just as a gateway. For the purposes of a large load (complex networks, complex routing) are advised to consider the selection of adequate resource PC Based on the test results can be summarized as follows: The system can use a billing system that can regulate and restrict the clients to use the internet access in which all the parties in this case the client and the management there are no losers, in other words mutually beneficial.